STRATEGI PESANTREN DALAM MENINGKATKAN SUMBER DAYA SANTRI YANG BERKEMAJUAN (STUDI PADA PONDOK PESANTREN PERKAMPUNGAN MINANGKABAU) - Nurfarida Deliani; Ahmad Putra; Nona Nurfadhilla; Anggi Fitria; Candra Halim; Ira Sumarni; Adi Sahyogi (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2022)
This research is motivated by the motivation of the Minangkabau Perkampungan Islamic Boarding School in raising the image of the pesantren in this progressive era. This effort has become a pesantren strategy in balancing the busyness of students in the pesantren by developing existing resources. Thus, students are equipped with skills and expertise that are very useful for their future. This study uses a descriptive qualitative method with the research subject being the Leaders of Islamic Boarding Schools and the ranks who have contributed to developing progressive santri resources. The results of this research include: first, Islamic boarding schools instill three pillars of education which include: the application of adab, the application of tahfidz and the application of life skills. Second, Islamic boarding schools develop existing resources so that they educate students in recognizing businesses that have a good impact on the future, especially those that provide results and contribute to living life later.